Carbohydrate is a diverse compound in the body and can be as glycoconjugate which bound to protein in proteoglycan and glycoprotein shape, and bound to lipid in glycolipid shape as well. The study was conducted to get information image of pattern distribution of the glycoprotein at stomach gland from various age levels at Macaca fascicularis (Mf) after and before bearing. Gastric specimen was collected processed through microtechnique procedure, followed by histochemistry Lectin staining to det - Erdiansyah Rahmi; Dondin Sajuthi; Srihadi Agungpriyono; Erni Sulistiawati (Pusat Studi Satwa Primata LPPM-IPB, 2009)
Carbohydrate is a diverse compound in the body and can be as glycoconjugate which bound to protein in proteoglycan and glycoprotein shape, and bound to lipid in glycolipid shape as well. The study was conducted to get information image of pattern distribution of the glycoprotein at stomach gland from various age levels at Macaca fascicularis (Mf) after and before bearing. Gastric specimen was collected processed through microtechnique procedure, followed by histochemistry Lectin staining to detect glycoprotein from stomach. Observation result of given score subjectively into four categories: (-) none/negatif, (+) low, (++) medium,and (+++) height. The results obtained were tabulated and analyzed diskriptively. We found that glycoproteins complex exist in the glandullar stomach of long tailed macaques are mannose, glucose, galactose, N-acetil-D-glocosamine and N-acetil-D-galactose all of these glycoproteins complex was observed at age foetus 70 days. Glycoprotein can act as energy resource used for grouht and protections toward stomach. Keywords: glycoprotein, lectin, stomach gland, Macaca fascicularis